FEMA GRAS assessment of natural flavor complexes: Clove, cinnamon leaf and West Indian bay leaf-derived flavoring ingredients. (November 2020) - Gooderham, Nigel J.; Cohen, Samuel M.; Eisenbrand, Gerhard; Fukushima, Shoji; Guengerich, F. Peter; Hecht, Stephen S.; Rietjens, Ivonne M.C.M.; Rosol, Thomas J.; Davidsen, Jeanne M.; Harman, Christie L.; Murray, Ian J.; Taylor, Sean V.
Abstract: In 2015, the Expert Panel of the Flavor and Extract Manufacturers Association initiated the safety re-evaluation of over 250 natural flavor complexes (NFCs) used as flavor ingredients. This publication, 4th in a series focusing on the safety evaluation of NFCs, presents an evaluation of NFCs rich in hydroxyallylbenzene and hydroxypropenylbenzene constituents using a procedure initially published in 2005 and updated in 2018 that evaluates the safety of naturally occurring mixtures for their intended use as flavoring ingredients. The procedure requires the characterization of the chemical composition for each NFC and subsequent organization of the constituents into defined congeneric groups. The safety of each NFC is evaluated using the conservative threshold of toxicological concern (TTC) approach together with studies on absorption, metabolism and toxicology of the NFC and its constituent congeneric groups. By the application of this procedure, seven NFCs, derived from clove, cinnamon leaf and West Indian bay leaf were affirmed as "generally recognized as safe (GRAS)" under their conditions of intended use as flavor ingredients. An eighth NFC, an oleoresin of West Indian bay leaf, was affirmed based on its estimated intake, which is below the TTC of 0.15 μg/person per day for compounds with structural alerts for genotoxicity. Highlights: Safety evaluation of clove, cinnamon leaf and West Indian Bay leaf-derived flavoring ingredients. Evaluation used procedure developed by the FEMA Expert Panel for natural flavors. FEMA GRAS status determined/affirmed for 8 natural flavor complexes.